GAMBARAN TINGKAT PENGETAHUAN IBU TENTANG PEMBERIAN ASI EKLUSIF DI BPM KECAMATAN BEKASI UTARA 2018 - Cik Angkut; Aan Kurniati (LPPM STIKes Prima Indonesia, 2020)
This study aims to describe the level of knowledge of mothers about exclusive breastfeeding at BPM in NorthBekasi District in 2018. It was using descriptive cross-sectional method. The population in this study were mothersof reproductive age who had given birth in the last one year in the North Bekasi BPM region, amounting to 305people. The sample used was Accidental, amounting to 75 people. The results of research conducted by researchersfound that most nursing mothers with good knowledge were 61 people (81.3%), while mothers with sufficientknowledge were 13 people (17.3%), and mothers with less knowledge were one person (1, 3%). The conclusion ofthis study shows that the level of education was one of a lot of factor that can influence a mother can provideexclusive breastfeeding to his baby until the age of 6 months. Working mothers need support from all parties so thattheir knowledge increases.